To Work or Not to Work? Effects of Temporary Public Employment on Future Employment and Benefits - Eva Mörk; Lillit Ottosson; Ulrika Vikman (Institute of Labor Economics (IZA), 2022)
We evaluate a temporary public sector employment program targeted at individuals with weak labor market attachment, applying dynamic inverse probability weighting to account for dynamic selection. We show that the program is successful in increasing employment and reducing social assistance. However, being at a regular workplace seems crucial: we find negative employment effects for participants employed at a workplace created especially for the purpose. The decrease in social assistance is to some extent countered by an increase in the share receiving unemployment insurance benefits, indicating that municipalities are able to shift costs from the local to the central budget.
Keywords: H75; I38; J45; 330; public sector employment programs; social assistance; cost-shifting; dynamic inverse probability weighting